Clinical outcomes and relapse patterns in pediatric acute leukemia patients undergoing hematopoietic cell transplantation: a multicenter Brazilian experience - Polliany Roberta Dorini Pelegrina; Polliany Roberta Dorini Pelegrina; Rita de Cassia Barbosa Tavares; Adriana Mello Rodrigues; Adriana Mello Rodrigues; Adriana Mello Rodrigues; Gisele Loth; Gisele Loth; Gisele Loth; Samantha Nichele; Samantha Nichele; Cilmara Kuwahara; et al. (Frontiers in Pediatrics)
BackgroundHematopoietic cell transplantation (HCT) represents a well-established therapeutic strategy for high-risk leukemia, though post-transplant relapse remains a significant challenge, particularly in resource-limited settingsProcedureIn this retrospective study, we analyzed medical records of 310 pediatric patients (age < 18 years) who underwent HCT for acute leukemias at four Brazilian institutions between 2010 and 2019.ResultsThe cohort included patients with acute lymphoblastic leukemia (ALL; 74.2%) and acute myeloid leukemia (AML; 25.8%). The median age was 9.52 years (range: 0.25–17.97), with male predominance (68.3%). Total body irradiation (TBI)-based conditioning was utilized in 72.6% of cases, and bone marrow served as the predominant graft source (74.5%). Prior to transplantation, 46.5% of patients were in first complete remission. Post-transplant relapse occurred in 36.7% of patients at a median of 245 days (range: 38–2,505). With a median follow-up of 2,019 days (5.5 years), overall survival was 69.3% at one year, declining to 62.4% at two years. The cumulative incidence of relapse was 12.6%, 28.8%, and 33.4% at 100 days, one year, and two years post-HCT, respectively. Adjusted analysis revealed increased relapse risk in patients with mixed donor chimerism, positive minimal residual disease (MRD) status before HCT, and disease status beyond first complete remission (including CR2, advanced disease, and refractory disease).Conclusion(s)These findings underscore the elevated relapse risk associated with advanced disease status, positive pre-HCT MRD, and mixed donor chimerism post-transplant. Future interventions should prioritize improving diagnostic capabilities, expanding access to modern treatment protocols, and facilitating early referral to transplant centers, particularly for aggressive disease presentations.